A knot in the gut: A paediatric post-mortem CT diagnosis. Issue 4 (December 2015) - Vester, M.E.M.; van Rijn, R.R.
Abstract: We present a case of a previously healthy, five month old boy who, after a short history of mild abdominal complaints died unexpectedly. In this case no parental permission for a conventional autopsy could be obtained on religious grounds, but a and post-mortem CT was consented to and performed. Based on the clinical evaluation combined with PMCT findings a probable cause of death, ileosigmoid knotting, could be established.